Faktor-Faktor yang Berpengaruh Terhadap Kepuasan Kerja dan Kinerja Manajer Perusahaan Manufaktur - Abriyani Puspaningsih (Jurnal Akuntansi dan Auditing Indonesia, 2004)
This research is aimed to expose the effect of some variables on the job satisfaction and the performance of manufacturing company managers. Respondents in this research were the managers of the big scale manufacturing companies in Indonesia. The data in this research were collected through mail quesionares. The data analysis was carried on by regression analysis.The results from the analysis showed that the effect of some variables (budgetary par¬ti¬cipation, budget goal clarity, budgetary feedback, education and job experience) on the job satis¬faction is 49,1 percent. This indicates that 50,9 percent of the job satisfaction is affected by other variables, which were not used in this research.The other results from the analysis showed that the effect of some variables (budgetary participation, budget goal clarity, budgetary feedback, education and job experience) on the per¬formance of manager is 45.5 percent. This indicates that 54.5 percent of the performance of man¬ager is affected by other variables which were not used in this research.Key words:    budgetary participation, budget goal clarity, budgetary feedback, education, job experience, job satisfaction and the performance of managers.